Ecological and Evolutionary Dynamics of Aresian and Erosian Economy - Lázár, Imre (International Journal of Industrial Engineering and Management, 2014)
In this paper we explore the ecodynamics of economic transformation of Central-East –European late socialist industries under the pressure of globalization. We use both term ARES and Eros in allegoric sense and as an acronym of Accumulation, Risk, Environmental degradation In this framework we deconstruct the process of the neoliberal transformation of local economies. Deconstruction of informational, technological and social dynamism also helps to reveal the hierarchical ranks of the four environmental actors feedingt the ARESian dynamics of contemporary economical and social phenomena. Article history: Received (05.12.2013); Revised (03.03.2014); Accepted (15.03.2014)